Advertising campaign and the beneficial of art therapy in reducing stress and emotional problems / Hibatur Rahman Mat Tahir - Mat Tahir, Hibatur Rahman (2013)
The main objective in this research is to study about the effectiveness of art therapy campaign and its benefit towards society. Art therapy is not well known in Malaysia, this is because the approach or information given to Malaysian is still not enough. So this research is more to introduce the beneficial of art therapy in reducing stress and emotion problems among the people in Malaysia